2013
DOI: 10.1371/journal.pone.0066474
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin Fragments and a Specific Gliadin 33-mer Peptide Close KATP Channels and Induce Insulin Secretion in INS-1E Cells and Rat Islets of Langerhans

Abstract: In non-obese diabetic (NOD) mice, diabetes incidence is reduced by a gluten-free diet. Gluten peptides, such as the compound gliadin, can cross the intestinal barrier and may directly affect pancreatic beta cells. We investigated the effects of enzymatically-digested gliadin in NOD mice, INS-1E cells and rat islets. Six injections of gliadin digest in 6-week-old NOD mice did not affect diabetes development, but increased weight gain (20% increase by day 100). In INS-1E cells, incubation with gliadin digest ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
2
38
1
Order By: Relevance
“…This raised beta-cell activity may contribute to an increase in surface Ags recruiting immune cells to the islets, along with increased secretion of cytokines. These findings correlate with a previous study showing that gliadin increases insulin secretion in rat islets and the INS-1E cell line [9].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This raised beta-cell activity may contribute to an increase in surface Ags recruiting immune cells to the islets, along with increased secretion of cytokines. These findings correlate with a previous study showing that gliadin increases insulin secretion in rat islets and the INS-1E cell line [9].…”
Section: Discussionsupporting
confidence: 93%
“…This raised beta-cell activity may contribute to an increase in surface Ags recruiting immune cells to the islets, along with increased secretion of cytokines. These findings correlate with a previous study showing that gliadin increases insulin secretion in rat islets and the INS-1E cell line [9].In vivo, we found several gluten-induced effects in immunocompetent BALB/c mice and diabetes-prone NOD mice. We showed that an STD gluten-containing diet increased the amount of NKp46…”
supporting
confidence: 93%
See 3 more Smart Citations